تأثير بعض الأوساط الزراعية في نمو بادرات نخيل البلح وتطورها Phoenix dactylifera (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
استخدمت في البحث بادرات نخيل التمر، لاختبار مدى كفاءة ستة أوساط زراعية (تربة، تورف ورمل وخلائطها) في نمو هذه البادرات وتطورها. تم قياس بعض الخصائص الفيزيائية والكيميائية لهذه الأوساط خلال منتصف موسم النمو ونهايته. بينت التجارب أن درجات الحموضة في الأوساط المستخدمة تقع ضمن المجال النموذجي باستثناء التورف والرمل، كما سجل فقر في الملوحة في الأوساط المستخدمة. وقد ظهر أن التورف يحسن مستوى التغذية المائية للأوساط المعدنية المخلوطة به، ويؤمن ظروف نمو أفضل للجذور. وقد أعطى وسطا التورف والتربة أعلى معدل في متوسط طول النبات، كما أن وسط التورف أعطى أفضل الأوزان الجافة للمجموع الخضري، مقابل جميع الأوساط الأخرى، وكذلك التورف. وكانت خلائطه الأفضل في متوسط عدد أوراق البادرات. وبشكل عام لم تؤثر الأوساط الخليطة في طول المجموع الجذري. أما الرمل فكان الأفضل بالمقارنة بالأوساط الأخرى، من حيث طول الجذور وخليط التورف والرمل، وكان الأفضل بالنسبة لعدد الجذور على النبات الواحد.Date palm (Phoenix dactylifera) seedlings were used in this study to test the efficiency of six agricultural media (soil, peat, sand and their mixtures) in growing and developing them. Some of the physical and chemical media properties were measured during middle and final of the growing season. The experiments were standard according to acidity steps for the investigated media except for peat and sand. A salinity deficiency was recorded in the investigated media. Peat improved the aqueous feeding level of metallic media mixed with it, and gave better growing conditions for roots. The peat and soil media gave the highest average of plant length mean. Peat also gave the best dry weights of whole leaves and stems. Compared with other media, peat and its mixtures were also the best according to number of seedlings leaves. The mixed media did not generally affect the root system length. Sand was the best according to roots length; the mixture of peat and sand according to roots number for each plant compared with other media.